2014
DOI: 10.1088/0963-0252/23/5/054014
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal arrayed patterns with bright and dark spots observed in a compact plasma reactor based on a piezoelectric transformer

Abstract: In this paper, we describe the formation of hexagonal arrayed patterns in a compact plasma reactor that consists of a piezoelectric transformer (PT) and a dielectric electrode. A high voltage induced on the PT surface by the piezoelectric effect generated diffuse glow-like and patterned dielectric barrier discharges (DBDs) in a gap. Vacuum ultraviolet (VUV) spectroscopy was applied to observe light emitted from Xe * 2 and Ar * 2 excimers, which were formed in a He-Xe mixture and pure Ar, respectively. Peaks at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…It should be noted that besides the SOP formed at the plasma-liquid (or even solid) interface, patterns can be formed in the plasma as seen from the lateral side of the discharge chords. [10][11][12] In parallel to experimental works, SOPs have been the subject of several theoretical studies considering various discharge configurations such as dielectric barrier discharge (DBD) discharge, 39,40 arc discharge, 41,42 and DC glow discharge. 43,44 Benilov modeled SOPs in DC glow discharge and/or arc discharge based on the first-principles equations containing all the relevant physical mechanisms and proposed that the cathode sheath instability is responsible for SOP formation on the cathode.…”
Section: Table 1 Types Of Plasma Devices With Formed Self-organized mentioning
confidence: 99%
“…It should be noted that besides the SOP formed at the plasma-liquid (or even solid) interface, patterns can be formed in the plasma as seen from the lateral side of the discharge chords. [10][11][12] In parallel to experimental works, SOPs have been the subject of several theoretical studies considering various discharge configurations such as dielectric barrier discharge (DBD) discharge, 39,40 arc discharge, 41,42 and DC glow discharge. 43,44 Benilov modeled SOPs in DC glow discharge and/or arc discharge based on the first-principles equations containing all the relevant physical mechanisms and proposed that the cathode sheath instability is responsible for SOP formation on the cathode.…”
Section: Table 1 Types Of Plasma Devices With Formed Self-organized mentioning
confidence: 99%
“…Thus, one can conclude that fluorescence from SS depends on VUV caused by resonance radiation from Ar( 3 P 1 ) and Ar( 1 P 1 ) generated by DBD and APJ. However, considering that these experiments were conducted under atmospheric pressure and that emission from the xenon excimer Xe 2 * was stronger than resonance light observed by the authors in He‐Xe gas mixture, 27 there is a possibility of VUV at 126 nm emitted by the argon excimer Ar 2 * 28,29 . We would like to wait for spectroscopic results.…”
Section: Resultsmentioning
confidence: 93%
“…However, considering that these experiments were conducted under atmospheric pressure and that emission from the xenon excimer Xe 2 * was stronger than resonance light observed by the authors in He-Xe gas mixture, 27 there is a possibility of VUV at 126 nm emitted by the argon excimer Ar 2 *. 28,29 We would like to wait for spectroscopic results. Kuwahara and Ohyama 11 conducted APJ experiments aimed at hydrophilization of quartz glass 11 and reported that hydrophilization was different at the central and peripheral parts of the jet.…”
Section: Vuv Detection Along Apj Flowmentioning
confidence: 99%
“…This is the case, for example, of the irregular plasma sheath developed at metalinsulator lateral junctions, 42,43 the plasma formation and alignment of carbon nanotubes, 44 or the generation of plasmas by the so-called piezoelectric transformers. 27,28 Also related with the local densification resulting from the model proposed in Fig. 4 is the known large area thin film densification occurring when biasing a substrate during MS deposition or under the bombardment with accelerated ions provided by an external source during Ion Beam Assisted Deposition (IBAD).…”
Section: Materials Horizons Accepted Manuscriptmentioning
confidence: 99%
“…26 Plasma sheaths are always present when a thin film is deposited via any plasma driven procedure. 25 Despite the growing emergence of AWs-plasma interactions studies with promising technological implications, 27,28 the involvement of these interactions in the deposition and nano-structuration of thin films has been largely overlooked by the scientific community (to our knowledge, except for an early work by Takahashi et al 29 that will be briefly discussed later, no other attempts have addressed this problem). In the present work we report that the use of Lamb AWs significantly influence the 2D patterning of nanostructure, crystal structure and physical properties of plasma thin films.…”
Section: Introductionmentioning
confidence: 99%